The Sepedi Helper Writing Assistant: A User Study. Issue 2 (4th May 2019) - Prinsloo, Danie; Taljard, Elsabé
Abstract: This article reports on an evaluation of the Sepedi Helper (http://www.sepedihelper.co.za/ ), an online writing assistant. The focus of the evaluation is on the verbal moods in Sepedi (Northern Sotho). The evaluation takes the form of a user study, and data collection was done by means of a questionnaire, administered to 81 first- and second-year students at a tertiary institution who do not have Sepedi as their strongest/home language. Analysis of the data includes identification of the most problematic moods and constructions and typical errors made by the students, and an evaluation of the contribution made by the Sepedi Helper. This writing assistant is a work in progress, with the developers' ultimate aim being to compile a complete online grammar for Sepedi. The results of the evaluation indicate that the Sepedi Helper meets its stated aims, namely to confirm correct responses, correct errors, and identify the most common errors made by learners of Sepedi.